2020
DOI: 10.3390/ijms21082833
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin-Based Peptide (ADP355) Inhibits Transforming Growth Factor-β1-Induced Fibrosis in Keloids

Abstract: Keloids, benign cutaneous overgrowths of dermal fibroblasts, are caused by pathologic scarring of wounds during healing. Current surgical and therapeutic modalities are unsatisfactory. Although adiponectin has shown an antifibrotic effect, its large size and insolubility limit its potential use in keloid treatment. We investigated the effect of a smaller and more stable adiponectin-based peptide (ADP355) on transforming growth factor β1 (TGF-β1)-induced fibrosis in a primary culture of keloid fibroblasts prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Lesions were obtained for further analysis 7 days after the final treatment. Measurement of graft weight and western blot analysis of xenotransplant tissue was carried out according to a previously described protocol ( 14 ). The study was approved by the Institutional Care and Use Committee (IACUC) of Seoul National University, and the number of animals used was kept to a minimum to reduce suffering, according to the protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Lesions were obtained for further analysis 7 days after the final treatment. Measurement of graft weight and western blot analysis of xenotransplant tissue was carried out according to a previously described protocol ( 14 ). The study was approved by the Institutional Care and Use Committee (IACUC) of Seoul National University, and the number of animals used was kept to a minimum to reduce suffering, according to the protocol.…”
Section: Methodsmentioning
confidence: 99%
“…The keloid xenograft mouse model was performed as previously described [20]. Briefly, the keloid tissues were cut into approximately 5 × 5 × 5 mm sections, and the weight was ranged from 0.08 to 0.1 g per tissue block.…”
Section: Keloid Xenograft Mouse Modelmentioning
confidence: 99%
“…The mechanism of fibrosis is similar for tissues and organs and consists of the following four sequential stages: (a) organ or tissue injury; (ii) inflammatory reactions of effector cells; (c) increased synthesis of extracellular matrix (ECM); and (d) tissue and organ structural remodelling disorders that ultimately lead to organ failure. APN and APN receptor agonists have strong anti‐fibrotic activity in the liver, lung, heart, skin and other organs and tissues 12‐16 . Recent studies found that APN also plays an important role in the process of renal fibrosis (Figure 1).…”
Section: Role Of Apn In Renal Fibrosismentioning
confidence: 99%
“…First, it promotes fatty acid oxidation and glucose metabolism and also regulates blood lipid metabo- lung, heart, skin and other organs and tissues. [12][13][14][15][16] Recent studies found that APN also plays an important role in the process of renal fibrosis (Figure 1). pathway has potential for the treatment of chronic renal fibrosis.…”
mentioning
confidence: 99%